2017
DOI: 10.1007/s00038-017-0971-8
|View full text |Cite
|
Sign up to set email alerts
|

Setting up a community-based cervical screening service in a low-income country: a pilot study from north-western Tanzania

Abstract: ObjectivesTo report the results of a pilot study for a service for cervical cancer screening and diagnosis in north-western Tanzania.MethodsThe pilot study was launched in 2012 after a community-level information campaign. Women aged 15–64 years were encouraged to attend the district health centres. Attendees were offered a conventional Pap smear and a visual inspection of the cervix with acetic acid (VIA).ResultsThe first 2500 women were evaluated. A total of 164 women (detection rate 70.0/1000) were diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
5
1
1
Order By: Relevance
“…The differences with low VIA positive screening results could be explained by the high density in primary health care facilities including HIV clinics in these settings [32]. This might also influence the lower VIA positivity in our study with only 2.6% of HIV infected participants, compared with the study from Mara where 8.2% were infected with HIV [38]. Furthermore, PrevACamp findings showed no significant difference between residence status and VIA-positivity.…”
Section: Need For Extended Cancer Education and Screening Programscontrasting
confidence: 60%
See 1 more Smart Citation
“…The differences with low VIA positive screening results could be explained by the high density in primary health care facilities including HIV clinics in these settings [32]. This might also influence the lower VIA positivity in our study with only 2.6% of HIV infected participants, compared with the study from Mara where 8.2% were infected with HIV [38]. Furthermore, PrevACamp findings showed no significant difference between residence status and VIA-positivity.…”
Section: Need For Extended Cancer Education and Screening Programscontrasting
confidence: 60%
“…Cervical cancer may impact HIV infected women differently than other populations. Studies show that women infected with HIV are more likely to appear with cervical cancer disease later in life [ 38 , 39 ]. Bateman et al assessed barriers to cervical cancer screening among HIV infected women in Tanzania and found that women had high misconceptions of cervical cancer screening and felt that diagnosis may lead to death, hence hindering women from seeking health care [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative VIA positivity was 9.2% (n = 4062) (Table 1). HIV infection was significantly associated with precancerous changes, with 16.8% of HIV+ women also VIA+ (523/3122) (Anderson et al, 2015; Bernstein et al, 2018; Dartell et al, 2014; Baldur-Felskov et al, 2018; Masalu et al, 2017; Chambuso et al, 2017; Kafuruki et al, 2013) (Table 2). High grade dysplastic lesions were often inferred by VIA screening results due to infrequency of pathologic confirmation.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, treatment failure due to loss to follow-up was a common trend across the cervical pre-cancer and cancer care continuum. Masalu et al found that 28.8% of women did not receive cryotherapy for significant VIA+ lesions (Masalu et al, 2017). A second study demonstrated that receiving immediate treatment for VIA+ lesions in a single visit resulted in significant reduction in loss to follow-up, as 82% of those who postponed cryotherapy did not return for the procedure (Anderson et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The VIA test is one of the most widespread methods because it is the easiest to perform with a "screen-and-treat" approach. Some studies have reported a similar accuracy of the cervical smear and VIA test on women who are positive for HIV 19. By contrast, most of the studies have reported a high inter-operator variability, underlying the low accuracy and reproducibility of this test 14,20.…”
mentioning
confidence: 99%